MEMBANGUN KEBERSAMAAN UMAT HINDU KABUPATEN BLITAR - Sujaelanto (Widya Aksara : Jurnal Agama Hindu, 2025)
Religion is not only a guide for each person's personal life but also serves as a social glue for socio-religious life in society. However, in reality, religion also contributes to conflict and division when its teachings are interpreted in an incomprehensible manner. In today's world, the wealthy, who should be helping, instead expect to be helped. The Hindu concept of "punia" teaches us to give a portion of our wealth so that others can enjoy it. Is giving part of one's possessions based on religious obedience or is there something else that motivates someone to give "punia"? This paper will present how the social dimension of "punia" fosters unity among Hindus in Blitar Regency. This issue is analyzed and explained using semiotic theory. The analysis reveals that "punia" is a teaching with both social and spiritual dimensions. Socially, "punia" fosters attitudes and behaviors that care for the needs of others. Spiritually, "punia" serves as self-control against greed. Based on this concern, Hindus voluntarily donate a portion of their wealth for social purposes greater than their own. Offerings of alms (punia) are given to groups or individuals in need or underprivileged, but are also undertaken as an effort to meet the needs of socio-religious activities and/or to build social and religious facilities. Offerings are not only material but can also be expressed through labor, knowledge, skills, moral encouragement, and sense control. Offerings are carried out based on religious teachings and humanitarian values. The awareness and concern for offering alms (punia) among Hindus demonstrates the community's enthusiasm for practicing religious teachings.